Student-led honor codes as a method for reducing university cheating - David A. Rettinger; Douglas Searcy (Economic and Environmental Studies (E&ES), 2012)
As academic dishonesty is perceived to be on the rise in European universities, creative approaches to supporting integrity are being considered. In the U. S., some universities approach the issue by giving students more, not less, control over their academic lives. Student-led honor systems provide students a means of creating a community at their university that values academic integrity and enforces it as a social norm rather than as an abstract rule. This paper outlines the history and functioning of such programs, provides empirical support for their effectiveness, and a case study of one student-led honor system, at the University of Mary Washington.
Keywords: 330; academic integrity; case study; cheating; plagiarism; moral code